Comparison of a closed-loop control by means of high-fidelity and low-fidelity coupled CFD/RBD computations. (August 2020) - Franze, Marius
This work compares the principle of a basic fin-controlled sounding rocket with coupled computational fluid dynamic and rigid body dynamic simulations of two coupling environments: (1) a low-fidelity approach using Missile DATCOM as semi-empirical aerodynamic solver, and (2) a high-fidelity approach using DLR TAU as URANS CFD code. The flight mechanics solver REENT is used in both cases. A closed-loop flight path control is developed and adjusted via low-fi simulations and then verified via high-fi simulations. For simple roll and pitching maneuvers the environments match well, whereas differences can be seen in complex maneuvers, e.g. body–body interactions of separation procedures.